1972
DOI: 10.4039/ent1041251-8
|View full text |Cite
|
Sign up to set email alerts
|

A CHEMICALLY DEFINED, SYNTHETIC MEDIUM THAT INDUCES OVIPOSITION IN THE PARASITEITOPLECTIS CONQUISITOR(HYMENOPTERA: ICHNEUMONIDAE)

Abstract: A chemically defined, synthetic medium that induces oviposition in the parasite Itoplectis conquisitor (Say) has been developed. The medium contains serine (0.5 M), arginine (0.05 M), leucine (0.065 M), and magnesium chloride (0.025 M); and it is more effective than host haemolymph in inducing oviposition. This completely artificial oviposition stimulant was developed to facilitate the mass rearing of the parasite on an artificial diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…Arthur et al, (1972) found that Mg 2÷ enhanced the ovipositional activity of a mixture of 3 amino acids and that Ca 2÷ inhibited oviposition by Itoplectis conquisitor (Say) in an artificial larva. Arthur et al, (1972) found that Mg 2÷ enhanced the ovipositional activity of a mixture of 3 amino acids and that Ca 2÷ inhibited oviposition by Itoplectis conquisitor (Say) in an artificial larva.…”
Section: Discussionmentioning
confidence: 96%
“…Arthur et al, (1972) found that Mg 2÷ enhanced the ovipositional activity of a mixture of 3 amino acids and that Ca 2÷ inhibited oviposition by Itoplectis conquisitor (Say) in an artificial larva. Arthur et al, (1972) found that Mg 2÷ enhanced the ovipositional activity of a mixture of 3 amino acids and that Ca 2÷ inhibited oviposition by Itoplectis conquisitor (Say) in an artificial larva.…”
Section: Discussionmentioning
confidence: 96%
“…However, addition of trehalose restored much of the activity, indicating a synergistic effect by the sugar. Trehalose had little activity alone as an ovipositional stimulant, but it did increase oviposition of I. conquistor when added to solutions of the amino acids serine and arginine (Arthur et al 1972).…”
Section: Resultsmentioning
confidence: 99%
“…The pupal parasitoid Itoplectis conquistor (Say) was stimulated to oviposit by hemolymph or selected amino acids such as serine, arginine, and by magnesium chloride placed into parafilm tubes (Arthur et al 1972). The other parasitoid was an insect egg parasitoid- Rajendram & Hagen (1974) reported that saline or saline buffers stimulated oviposition of Trichogramma californicum Nagaraja & Nagarkatti into artificial I This article reports the results of research only.…”
Section: The Parasitoid Microplitis Croceipesmentioning
confidence: 99%
“…On the other hand, other chemicals may inhibit the ovipositional activity of KC1-MgSO4 solutions. For example, Ca 2 § inhibits oviposition into artificial hosts by T. pretiosum (Nettles et al, 1983) and by Itoplectis conquisitor (Say) (Arthur et al, 1972). Inhibition of oviposition may have at least partially accounted for the results obtained by House (1978) when he obtained only one I. conquisitor adult from an artificial diet used also as the oviposition Entomol.…”
Section: Introductionmentioning
confidence: 98%